Participatory Sense Making in Jazz Performance: Agents’ Expressive Alignment - Martínez, Isabel Cecilia (2017)
Relationships between musicians in Jazz performance can be understood as autonomous (turn-taking) versus simultaneous (playing joint), both assumed as social interactions that take place as to create meaning in a participatory way. To participate, in music performance, requires expressive alignment, in order to share the act of producing and perceiving sound and movement in an embodiedinter(en)acted phenomenological experience. In such context, interaction is assumed as an expressive exchange of meanings. In this work we study a trio jazz performance from an inter(en)acted approach, applying a methodological design that combines objective/statistical measures, and subjective/phenomenological data. An experiment that tested different conditions of turn-taking and/or joint playing of a Jazz standard was conducted in a recording studio session. All the performances were registered through audio/video media, and motion capture technology. In addition, in-depth interviews before playing/after recordings were conducted. Time series data related to sound and movement were analysed to study features of expressive alignment, accounting for descriptors of participatory sense-making. A Sense Granger measure was developed from Granger Causality measures in order to describe expressive alignment between-and-within performers. Significant differences were found in situations of turn-taking, and simultaneous playing between conditions. Results show that, beyond such differences, jazz musicians sustain interactional transactions based on their phenomenological experience of ‘going together in time’. Sense Granger measures serve to account for the ways expressive alignment evolves in time, providing significant cues that help understanding participatory sense making in jazz performance.